A multi-method study on the quality of the nurse work environment in acute-care hospitals: positioning Switzerland in the Magnet hospital research (Swiss Medical Weekly, 2012)
BACKGROUND: Magnet hospitals share nurse work environment characteristics associated with superior patient, nurse and financial outcomes. In Switzerland, however, it is uncertain how nurses appraise their work environments. OBJECTIVES: To describe the quality of the nurse work environment in 35 Swiss acute care hospitals and to benchmark findings based on international Magnet hospital research. METHOD: This study used two data sources: (1) the Swiss arm of the RN4CAST study; and (2) a structured literature review. Hospitals were categorised based on Magnet and non-Magnet data. Our outcome variable of interest was the quality of nurse work environment measured with the Practice Environment Scale of the Nurse Work Index (PES-NWI). RESULTS: We reviewed 13 American, Canadian, and Australian studies of acute-care hospitals. Three provided Magnet hospitals’ nurse work environment data, and all included non-Magnet hospitals’ data. Swiss hospitals’ evaluations on nurse work environment quality varied widely, but 25% achieved scores indicating “Magnet nurse work environments”. Swiss hospitals’ average “Nursing manager ability” subscale scores fulfilled Magnet hospital criteria, although “Nurse participation in hospital affairs” and “Nursing staffing and resource adequacy” scores neared non-Magnet levels. CONCLUSION: On average, our results indicated high quality nurse work environments in Swiss hospitals. Implementing Magnet model organisational principles might be a valuable approach for Swiss acute-care hospitals to both improve mixed and unfavourable nurse work environments and to improve nurse and patient outcomes. National benchmarking of nurse work environments and other nurse-sensitive indicators may facilitate evaluating the impact of current developments in Swiss healthcare.   Key words: nurse work environment; practice environment scale; Magnet status; acute care hospitals; Switzerland